Effectivness of Counseling on Mother\'s Breastfeeding Self-Efficacy - Soodabeh Aghababaei; Batoul Khodakarami; Maryam Farhadian; Marziyeh Kamali (Hamadan University of Medical Sciences, 2020)
Introduction: The present study was conducted to investigate the effect of breastfeeding counseling on the self-efficacy of lactating mothers. Methods: This study was conducted as a two-group clinical trial on 60 pregnant women referred to Malayer women's hospitals. Pregnant women were selected by available sampling method. Sampling was performed in two groups by block random method and the size of the blocks was considered as a multiple of the number of groups. Data collection tools included a demographic and midwifery characteristics questionnaire and a Fox and Dennis breastfeeding self-efficacy questionnaire. The intervention was carried out in accordance with GATHER's advisory principles. Maternal breastfeeding self-efficacy was assessed before intervention and one month after delivery in both groups. Results: The research units in the two control and test groups were homogeneous in terms of demographic characteristics. The change in mothers' breastfeeding self-efficacy score after intervention was significantly higher than before in test group (P<0.001). Conclusion: The results of the study showed that providing counseling has been very effective in increasing the self-efficacy of breastfeeding mothers and their performance.